2002
DOI: 10.1590/s0102-35862002000400006
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico e estadiamento do câncer de pulmão

Abstract: O câncer do pulmão pode apresentar-se sob diversas formas e vários são os meios de diagnosticá-lo. A escolha do melhor método para o seu diagnóstico depende de diferentes aspectos relacionados ao tumor, ao paciente e à habilidade da equipe médica. Dentre os métodos mais comumente utilizados para o diagnóstico do câncer do pulmão, podemos contar, além dos exames radiológicos, que não serão abordados neste artigo, a citologia do escarro, a broncofibroscopia, a punção aspirativa transtorácica e a toracoscopia, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
0
7
0
7
Order By: Relevance
“…In addition, it explains the reduced number of patients submitted to surgical treatment, which is indisputably indicated in the early stages and is indicated with restrictions in the more advances stages. (8,9) In the literature, only approximately 20% of the cases meet the operability criteria at the time of diagnosis, even in developed countries. In developing countries, this rate would be expected to be lower due to the fact that the underprivileged population has limited access to health care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it explains the reduced number of patients submitted to surgical treatment, which is indisputably indicated in the early stages and is indicated with restrictions in the more advances stages. (8,9) In the literature, only approximately 20% of the cases meet the operability criteria at the time of diagnosis, even in developed countries. In developing countries, this rate would be expected to be lower due to the fact that the underprivileged population has limited access to health care.…”
Section: Resultsmentioning
confidence: 99%
“…The current system was published in 1997 after a multicenter study involving more than 5,000 cases of lung cancer. (7,8) The treatment for lung cancer, when the tumor is still localized, without dissemination outside the lungs, is surgery. Tumors restricted to the lungs, in stages I and II, should be removed surgically.…”
Section: Introductionmentioning
confidence: 99%
“…The least common histological type was large cell carcinoma, a finding that is consistent with the literature. (3,4,9,11,12) One group of authors reported an increase in adenocarcinoma incidence, which can be higher than the incidence of squamous carcinoma. (18) According to Shields, (19) 30-50% are adenocarcinomas, 20-35% are squamous carcinomas, and 15-35% are small cell carcinomas.…”
Section: Resultsmentioning
confidence: 99%
“…Fiberoptic bronchoscopy is currently considered the primary method for evaluating the tracheobronchial tree in patients with suspected lung cancer. (4) In addition to allowing visualization of the lesion, the method allows the collection of cytological specimens (by bronchial lavage and bronchial brushing) and histological specimens (by endobronchial biopsy and transbronchial biopsy).…”
Section: Introductionmentioning
confidence: 99%
“…This also helps in the selection of the best treatment for each case of lung cancer. (1,2) In January of 2010, thoracic surgeons and pulmonologists were introduced to the seventh The revised tumor-node-metastasis staging system for lung cancer: changes and perspectives* which also allowed five years of follow-up prior to the analysis. Cases submitted to any treatment modality were included.…”
mentioning
confidence: 99%